Serum uric acid is associated with the progression of left ventricular diastolic dysfunction in apparently healthy subjects. (14th October 2021) - Yang, C.D; Wang, X.Q
Abstract: Background: Left ventricular (LV) diastolic dysfunction (LVDD) which is one of major characteristics of diastolic heart failure (HF) is also prevalent in the community. Patients with LVDD are predisposed to poor cardiovascular outcomes. Serum uric acid (SUA), an important component of metabolic disorders, has been shown to have close relationship with cardiovascular events including LVDD. In the present study, we sought to investigate whether SUA is a potential predictor of LVDD progression in relatively healthy subjects. Methods: From November 2018 to December 2019 in our Hospital, subjects who had physical examination were consecutively enrolled and followed up for ∼12 months. LVDD was graded by tissue doppler imaging (TDI). At baseline, only individuals with normal LV diastolic function or mild LVDD were finally enrolled and underwent repeated echocardiography and TDI assessment after follow-up. The incidence of LVDD progression, defined as LVDD grade 0–1 escalated to grade 2–3, and its relationship with SUA levels were analyzed. Multivariate regression models were constructed to test the predictive value of SUA for LVDD progression. Results: A total of 1082 subjects were included in the final analysis. During a mean follow-up of 12.6 (IQR 12.0–13.8) months, the incidence of LVDD progression was 37.6% and mean change in E/e' ratio was 1.18±1.85 cm/s, which was positively correlated with baseline SUV level (Spearman's r=0.140, P<0.001). In multivariate analysis, SUA was independently associated with LVDD progression after adjustment for traditional risk factors. The highest quartile of SUA corresponded to a 1.851-fold [95% CI 1.215–2.828] increased risk for progression of LVDD as compared to the lowest quartile. A 100 μmol/L increase in SUA conferred a 1.351-fold [95% CI 1.125–1.625] higher risk of LVDD progression when treated as continuous variable. Principal component analysis revealed SUA accounted for 14.7% of the variance in patients with LVDD progression, following insulin resistance and cholesterol factor which accounted for 27.9% and 19.0%, respectively. Conclusions: This study suggests that SUA is an independent predictor of LVDD progression in apparently healthy subjects. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China, Shanghai Municipal Commission of Health and Family Planning